A survey of working models of direct current motor in PWM rectifier – separately excited direct current motor system - Bùi Văn Vũ; Võ Phương; Đỗ Văn Cần; Lê Thái Hiệp (My University, 2021)
A survey of working models of direct current motor in PWM rectifier – separately excited direct current motor system
Keywords: Động cơ một chiều; Chỉnh lưu PWM; Kích từ độc lập